Non-invasive characterization of pleural and pericardial effusions using T1 mapping by magnetic resonance imaging. (30th July 2021) - Rosmini, Stefania; Seraphim, Andreas; Knott, Kristopher; Brown, James T; Knight, Daniel S; Zaman, Sameer; Cole, Graham; Sado, Daniel; Captur, Gabriella; Gomes, Ana Caterina; Zemrak, Filip; Treibel, Thomas A; et al.
Abstract: Aims: Differentiating exudative from transudative effusions is clinically important and is currently performed via biochemical analysis of invasively obtained samples using Light's criteria. Diagnostic performance is however limited. Biochemical composition can be measured with T1 mapping using cardiovascular magnetic resonance (CMR) and hence may offer diagnostic utility for assessment of effusions. Methods and results: A phantom consisting of serially diluted human albumin solutions (25–200 g/L) was constructed and scanned at 1.5 T to derive the relationship between fluid T1 values and fluid albumin concentration. Native T1 values of pleural and pericardial effusions from 86 patients undergoing clinical CMR studies retrospectively analysed at four tertiary centres. Effusions were classified using Light's criteria where biochemical data was available ( n = 55) or clinically in decompensated heart failure patients with presumed transudative effusions ( n = 31). Fluid T1 and protein values were inversely correlated both in the phantom ( r = −0.992) and clinical samples ( r = −0.663, P < 0.0001). T1 values were lower in exudative compared to transudative pleural (3252 ± 207 ms vs. 3596 ± 213 ms, P < 0.0001) and pericardial (2749 ± 373 ms vs. 3337 ± 245 ms, P < 0.0001) effusions. The diagnostic accuracy of T1 mapping for detecting transudates was very good for pleural and excellent for pericardial effusions, respectively [area under the curve 0.88, (95% CI 0.764–0.996), P = 0.001, 79% sensitivity, 89% specificity, and 0.93, (95% CI 0.855–1.000), P < 0.0001, 95% sensitivity; 81% specificity]. Conclusion: Native T1 values of effusions measured using CMR correlate well with protein concentrations and may be helpful for discriminating between transudates and exudates. This may help focus the requirement for invasive diagnostic sampling, avoiding unnecessary intervention in patients with unequivocal transudative effusions.